Business Ethics and Erm Influence on SME Company Performance Moderated by Business Strategy - Arnan Doman; Riris Rotua Sitorus (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Small and Medium Enterprises (SMEs) are one of the sectors not affected by several financial crises. However, Covid 19 pandemic has affected business performance due to restrictions on business activities. This Study aims to see Business Ethics, Enterprise Risk Management (ERM) influence company performance with moderation by SME Business Strategy in Indonesia. The research was conducted on Performing Loan borrowers at Bank Mandiri who came from seven provinces in Indonesia. According to Slovin Formula, the minimum sample size required is 362 companies from a population of 3,777. They have at least three years of business experience and annual sales of more than 5 billion rupiahs to a maximum of 50 billion rupiahs. The Structural Equation Model (SEM) method is used in quantitative research, and SmartPLS 3.0 and SPSS 26 software are used in data processing and analysis. Study results indicate that Business Ethics and Enterprise Risk Management positively and significantly influence company performance. In contrast, Business Strategy does not have a moderate relationship between Business Ethics and Enterprise Risk Management Company Performance. Based on the findings, in facing the economic crisis, SMEs must continue to apply Business Ethics, Business Risk Management, and other variables that affect their business performance appropriately.